Climate change risk reduction through readiness: an assessment of extreme temperature indices for Peninsular Malaysia - Husna Hasan; Nur Hanim Mohd Salleh (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Over the next century, people in many parts of the world will increasingly be confronted with the impacts of extreme climatic events. Such risks of extreme events can, fortunately, be reduced through readiness. Therefore, it is important to provide society and stakeholders in vulnerable sectors and regions with indicators and early warning information which will allow them to prepare properly and adequately. To improve readiness or preparedness for extreme temperature events in Peninsular Malaysia, twelve extreme temperature indices at ten selected states were developed and the significant trends of the indices using least square method analysed. The analysis results indicated that there were significant increasing and decreasing trends of extreme temperatures in some of the indices. The extreme temperatures affecting the northern, central and southern areas of Peninsular Malaysia were distinctly different from those of the eastern region, indicating that different levels of preparedness were in order.